Single-molecule manipulation quantification of site-specific DNA binding. (December 2019) - Zhao, Xiaodan; Guo, Shiwen; Lu, Chen; Chen, Jin; Le, Shimin; Fu, Hongxia; Yan, Jie
Abstract : The execution of functions on DNA relies on complex interactions between DNA and proteins in a sequence and structure dependent manner. Accurate quantification of the affinity and kinetics of these interactions is critical for understanding the molecular mechanisms underlying their corresponding biological functions. The development of single-molecule manipulation technologies in the last two decades has made it possible to apply a mechanical constraint to a single DNA molecule and measure the end-to-end extension changes with nanometer resolution in realtime. While it has been shown that such technologies can be used to investigate binding of ligands, which can be proteins or other molecules, to DNA in a fluorescence-label free manner, a systematic review on such applications has been lacking. Here, we provide a review on some of recently developed methods for fluorescence-label free single-molecule quantification of site-specific DNA binding by ligands and demonstrate their wide scope of applications using several examples of binding of ligands to dsDNA and ssDNA binding sites.